Genetic imprints of grafting in wild iron walnut populations in southwestern China - Jie Liu; Ephie A. Magige; Peng-Zhen Fan; Moses C. Wambulwa; Ya-Huang Luo; Hai-Ling Qi; Lian-Ming Gao; Richard I. Milne (BMC Plant Biology, 2023)
Abstract Background Anthropogenic activities are causing unprecedented loss of genetic diversity in many species. However, the effects on genetic diversity from large-scale grafting onto wild plants of crop species are largely undetermined. Iron walnut (Juglans sigillata Dode) is a deciduous nut tree crop endemic to southwestern China with a long history of cultivation. Due to the rapid expansion of the walnut industry, many natural populations are now being replaced by cultivars grafted onto wild rootstocks. However, little is known about the potential genetic consequences of such action on natural populations. Results We sampled the scion and the rootstock from each of 149 grafted individuals within nine wild populations of J. sigillata from Yunnan Province which is the center of walnut diversity and cultivation in China, and examined their genetic diversity and population structure using 31 microsatellite loci. Scions had lower genetic diversity than rootstocks, and this pattern was repeated in seven of the nine examined populations. Among those seven populations, AMOVA and clustering analyses showed a clear genetic separation between all rootstocks and all scions. However, the two remaining populations, both from northern Yunnan, showed genetic similarity between scions and rootstocks, possibly indicating that wild populations here are derived from feralized local cultivars. Moreover, our data indicated probable crop-to-wild gene flow between scions and rootstocks, across all populations. Conclusions Our results indicate that large-scale grafting has been causing genetic diversity erosion and genetic structure breakdown in the wild material of J. sigillata within Yunnan. To mitigate these effects, we caution against the overuse of grafting in wild populations of iron walnut and other crop species and recommend the preservation of natural genotypes through in situ  and ex situ conservation.